2018
DOI: 10.1111/mms.12510
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate and population size of Indo‐Pacific humpback dolphins (Sousa chinensis) in Xiamen Bay, China

Abstract: The survival rate and population size of Indo-Pacific humpback dolphins (Sousa chinensis) in Xiamen, China, were estimated from vessel-based surveys during 2007-2010. Over the course of 202 d (881.1 observation hours), 76 groups were observed, and 52 dolphins were successfully identified. The Cormack-Jolly-Seber model estimated a constant apparent survival of 0.948 (95% CI: 0.922-0.966).Based on the open/POPAN model, the population size was estimated at 70 individuals (95% CI: 63-88). To explore the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
(37 reference statements)
0
32
0
Order By: Relevance
“…In this study, we estimated the abundance of humpback dolphins exposed to the 3‐year survey ranged between 353 and 430 (mean = 389). This number cannot and should not be interpreted literally into a population size estimate, though POPAN modeling is frequently used to report population size (Chan & Karczmarski, ; Chen et al, , ; Xu et al, ). Chen et al () reported about 250 humpback dolphins in the Dafengjiang River Estuary, about 150 humpback dolphins in nearby Hepu Dugong Reserve habitat and, accordingly, concluded the population size is approximately 400 humpback dolphins in the northern Beibu Gulf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we estimated the abundance of humpback dolphins exposed to the 3‐year survey ranged between 353 and 430 (mean = 389). This number cannot and should not be interpreted literally into a population size estimate, though POPAN modeling is frequently used to report population size (Chan & Karczmarski, ; Chen et al, , ; Xu et al, ). Chen et al () reported about 250 humpback dolphins in the Dafengjiang River Estuary, about 150 humpback dolphins in nearby Hepu Dugong Reserve habitat and, accordingly, concluded the population size is approximately 400 humpback dolphins in the northern Beibu Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…Capture‐mark‐recapture exercises based on photo‐identification records were applied to understand residency pattern, emigration‐reimmigration dynamics, and abundance estimates (Chan & Karczmarski, ; Chen et al, ). Program SOCPROG (version 2.7; Whitehead, ) and program MARK (version 8.2; White & Burnham, ) were used to conduct the above analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coastline extends up to 3,752 km, and consists of many bays, including the Port of Shacheng, Sanduao waters, Luoyuan Bay, the Minjiang River estuary, Fuqing Bay, Xinghua Bay, Meizhou Bay, Quanzhou Bay, Xiamen Bay and Dongshan Bay. Fujian province is known as an important habitat for humpback dolphins (Chen et al, , ; Liu & Huang, ), and has rich marine resources (Sun & Zhang, ).…”
Section: Methodsmentioning
confidence: 99%
“…at least 89.2 km 2 land was reclaimed between 1955 and 2000 in Xiamen (Liu & Huang, ). Currently, humpback dolphins have been found to mainly inhabit Xiamen (Chen et al, , ; Liu & Huang, ), and no more than 30 individuals in the Quanzhou, Dongshan and Ningde waters have been observed (Chen, Zheng, Wang, Xu, & Yang, ; Wu et al, ). However, dedicated surveys in Fujian are lacking in most of the areas except for Xiamen, meaning that the large‐scale distribution patterns of humpback dolphins are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%